SYSTEMATIC APPROACH TO EVALUATION OF INDUSTRIAL MARKETS (INNOVATIVE ECONOMY, 2022)
Kostetska N.I. SYSTEMATIC APPROACH TO EVALUATION OF INDUSTRIAL MARKETSPurpose. The aim of the article is to study the peculiarities of functioning industrial markets, in particular the market of bread and bakery products, using a systematic approach.Methodology of research. Scientific works of scholars on the functioning of industrial markets are the theoretical and methodological bases of the research. The article uses general scientific methods of research such as comparison and theoretical generalization methods to study the essence of constituent elements of the paradigm; analysis and synthesis methods to identify the main factors that determine the peculiarities of the market structure, influence the behaviour of firms and market performance, as well as the role of government policy; abstract and logical methods to formulate the results of research into the structure of the bread and bakery products market.Findings. The article investigates the essence and constituent elements of the Structure – Conduct – Performance Paradigm. It considers the existing interrelationships between the market structure, the firms behaviour and performance taking into account the influence of the government on the activity of industrial markets and firms operating on them. The paper investigates peculiarities of the functioning of the industrial market of bread and bakery products in modern conditions of economic development taking into account the theoretical foundations of the Paradigm.Originality. The paper uses a systematic approach to the study of relationships between firms and the market where they operate taking into account the government influence. It develops the peculiarities of the application of the Structure – Conduct – Performance Paradigm for market research of bread and bakery products.Practical value. The obtained results of the research can be used in the development of recommendations for regulating the situation on the industrial market of bread and bakery products and improving the efficiency of the functioning of baking companies.Key words: industrial market, Structure – Conduct – Performance Paradigm, demand, supply, market structure, firm behaviour, market performance, government policy.
Keywords: industrial market; Structure – Conduct – Performance Paradigm; demand; supply; market structure; firm behaviour; market performance; government policy.